A methods engineering study on Gosons Food Corporation - Calong, Elaine (College of Engineering, 2004)
The proponents of this study laid the foundation for work measurement at Gosons Food Corporation, manufacturer of frozen siopao, siomai and other meat products. By conducting methods engineering study on the process, layout and working conditions of the bakery, documentation and examination of the production process and specifications took place, extending the study to all types and sizes of siopao whilst using problem analysis tools such as checklists and Job/Worksite analysis Guides to acquire data not only from the management but from the workers themselves. Taking into account the analysis of the workplace, tools and equipment of the company, the proponents of the study determined that due to the delays in the part of the suppliers and management to communicate with the workers regarding the schedule of daily production, ambient temperature of the workplace, interference in the layout, and low motivation of the workers due to undetermined system of wage incentives, the plant is generating products below its capacity, which was found to have lost three (3) mixes (equivalent to 750 units of the product) a day for special siopao and (1) mix for mini siopao (equivalent to 550 units). Moreover, there are proposals of bakery layout and house rules to assist in the implementation of a proposed system of scheduled production with the required number of workers for higher efficiency. The significance of this study lies on the fact that the company is moving towards expansion; Gosons Food Corporation is ajar to new methods, layout and other recommendations for further improvement.